2021
DOI: 10.1212/nxi.0000000000001074
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness and Serum NfL Explain Cognitive Dysfunction in Newly Diagnosed Patients With Multiple Sclerosis

Abstract: Background and ObjectivesTo determine the relative importance of global or regional MRI and blood markers of neurodegeneration and neuroaxonal injury in predicting cognitive performance for recently diagnosed patients with multiple sclerosis (MS).MethodsThirty-five newly diagnosed patients with relapsing-remitting MS (RRMS) and 23 healthy controls (HCs) simultaneously completed a full clinical and neuropsychological assessment, structural brain MRI, and serum neurofilament light chain (sNfL) level test. Linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…31 These findings may relate to the location of the primary auditory cortex within the TTG, and its role in attention and learning from auditory cues. 30,32 The longitudinal changes in predictor variables, including change in sNfL, were not independently associated with cognitive performance, beyond the variance accounted for by baseline predictors. This may in part reflect the hypothesis that clinical progression, such as cognitive decline, is primed by earlier neuroinflammation.…”
Section: Discussionmentioning
confidence: 86%
“…31 These findings may relate to the location of the primary auditory cortex within the TTG, and its role in attention and learning from auditory cues. 30,32 The longitudinal changes in predictor variables, including change in sNfL, were not independently associated with cognitive performance, beyond the variance accounted for by baseline predictors. This may in part reflect the hypothesis that clinical progression, such as cognitive decline, is primed by earlier neuroinflammation.…”
Section: Discussionmentioning
confidence: 86%
“…For diagnosis value analysis, 4 studies detected plasma NfL (pNfL) concentrations [ 26 , 34 , 36 , 43 ] and the others measured serum NfL (sNfL) levels. Two studies applied ECL method [ 10 , 11 ], one used ELISA [ 40 ], and the others adopted the highly sensitive SIMOA mothed for NfL measurements in blood. Ten studies enrolled age-matched controls with MS patients [ 13 , 28 , 32 , 34 37 , 40 , 44 , 45 ] and 7 recruited sex-matched controls [ 28 , 32 , 34 36 , 40 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies applied ECL method [ 10 , 11 ], one used ELISA [ 40 ], and the others adopted the highly sensitive SIMOA mothed for NfL measurements in blood. Ten studies enrolled age-matched controls with MS patients [ 13 , 28 , 32 , 34 37 , 40 , 44 , 45 ] and 7 recruited sex-matched controls [ 28 , 32 , 34 36 , 40 , 43 ]. The other 18 studies that did not declare whether controls were age-matched were then considered as not age-matched studies, even though there was no statistical difference of age at baseline comparison in some studies.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly in a longitudinal assessment, baseline NfL levels correlated with the presence and volume of baseline Gd+ lesion; however, serum NfL levels at 52 weeks was not associated with Gd+ lesions at 52 weeks 320 . Similarly, another survey found no correlation between serum NfL levels and the number of Gd+ lesions 276,330 .…”
Section: Mri Activity T1 T2 and Gadolinium Enhancing Lesionsmentioning
confidence: 94%
“…However, it has been suggested that a correlation between NfL levels and neuropsychological symptoms might exist. Accordingly, high serum NfL levels and cortical thickness have been reported to correlate with global neuropsychological performance measured by Brief Repeatable Battery of Neuropsychological Tests (BRB-N) and Paced Auditory Serial Addition Test (PASAT) 330 . In line with these results, a study on 39 patients showed an inverse association between CSF NfL levels and Brief International Cognitive Assessment for MS (BICAMS) test results in progressive but not RRMS 289 .…”
Section: Cognitive Impairmentmentioning
confidence: 99%